2020
DOI: 10.1002/for.2685
|View full text |Cite
|
Sign up to set email alerts
|

Predictive models for influence of primary delays using high‐speed train operation records

Abstract: Primary delays are the driving force behind delay propagation, and predicting the number of affected trains (NAT) and the total time of affected trains (TTAT) due to primary delay (PD) can provide reliable decision support for real-time train dispatching. In this paper, based on real operation data from 2015 to 2016 at several stations along the Wuhan-Guangzhou high-speed railway, NAT and TTAT influencing factors were determined after analyzing the PD propagation mechanism. The eXtreme Gradient BOOSTing (XGBOO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Then, we attempt to measure the effectiveness of the bias correction approaches in enhancing the prediction accuracy of the prediction models. The % Improvement in RMSE and R 2 is determined through the comparison between DMOLR with correction and the baseline model, that is DMOLR without any correction using eqn (4).…”
Section: Resultsmentioning
confidence: 99%
“…Then, we attempt to measure the effectiveness of the bias correction approaches in enhancing the prediction accuracy of the prediction models. The % Improvement in RMSE and R 2 is determined through the comparison between DMOLR with correction and the baseline model, that is DMOLR without any correction using eqn (4).…”
Section: Resultsmentioning
confidence: 99%
“…Ref. [ 7 ], on the other hand, employed predictive models based on high-speed train operation records to delve into the influence of primary delays, with a specific concentration on internal factors that contribute to delay severity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Li et al (2021) found that delays less than three minutes are most vulnerable to the period of delay occurrence. Li et al (2020b) discovered that the average number of affected trains was related to the severity of the delays, which increased with higher average numbers.…”
Section: Explainatory Variablesmentioning
confidence: 99%